PROBLEMATIC ISSUES OF COMBINED INTESTINAL INFECTIONS - V. V. Shkarin; O. A. Chubukova; A. S. Blagonravova; A. V. Sergeeva (Журнал инфектологии)
The  article  presents the  possible combinations of intestinal   infections of  various   etiologies, some   pathogenetic, clinical  and  epidemiological features and  problems of epidemiological surveillance and  control  of  associated infections.  Details  the  combination of typhoid fever,  shigelloses, salmonelloses, yersiniosis, pseudotuberculosis, rotavirus and norovirus infections between itself  and  other  infectious and parasitic diseases. Discusses the clinical  and  epidemiological features different combinations of intestinal infections. It is shown  that  the proportion of combined intestinal infections  can reach  to 48.9±3.3% in the structure of all associated  infections. The proportion of combination of two intestinal  infections pathogens was  29,2±6,5%, 3 agents and 10,3±4,3% and  4 pathogens and  5,9±11,6 percent. In the overall structure of the combination of intestinal anthroponoses with anthroponoses was 61,9±5,3%, anthroponoses with zoonoses was 31,1±5,0%, the other combinations (zoonoses and  zoonoses, zoonoses and  sapronoses, antroponoses with zoonoses and  sapronoses) of  7,0±9,3  percent. The  article raises  the  question of  the  need to  introduce into  existing regulatory framework the  new  scientific data  on the  whole range of features of the epidemiology of intestinal infections combined.